Day 4 Thu, October 01, 2020 2020
DOI: 10.2118/199999-ms
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Cyclic Gas Injection in the Gas Condensate Window of Unconventional Reservoirs

Abstract: Reservoirs such as Duvernay, Montney and Eagle Ford are segmented in different areas, ranging from predominantly dry gas regions, to wet gas and oil regions. Extensive research has focused on the application of enhanced recovery methods in the oil window of such reservoirs. In this paper, we discuss the application of enhanced recovery in the gas condensate window, with the objective to investigate the impact of diffusion on liquid dropout and vaporization on a matrix level. The Maxwell-Stefan e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Wan et al (2018) used nuclear magnetic resonance (NMR) technology to investigate porescale recovery mechanisms of cyclic nitrogen injection and revealed that the first few cycles provided the most accessible oil (Wan et al, 2018). Santiago and Kantzas (2020) performed a huff and puff gas injection simulation for an unconventional gas condensate reservoir (Santiago and Kantzas, 2020). They discovered that the higher number of cycles yields more efficient contact between the injected fluid and reservoir oil; nevertheless, they emphasized that extra cycles do not constantly enhance oil production.…”
Section: Introductionmentioning
confidence: 99%
“…Wan et al (2018) used nuclear magnetic resonance (NMR) technology to investigate porescale recovery mechanisms of cyclic nitrogen injection and revealed that the first few cycles provided the most accessible oil (Wan et al, 2018). Santiago and Kantzas (2020) performed a huff and puff gas injection simulation for an unconventional gas condensate reservoir (Santiago and Kantzas, 2020). They discovered that the higher number of cycles yields more efficient contact between the injected fluid and reservoir oil; nevertheless, they emphasized that extra cycles do not constantly enhance oil production.…”
Section: Introductionmentioning
confidence: 99%